Inhibitory Effect of Pioglitazone on Type-2 Diabetes Induced Nuclear Damages in Wistar Rats - SYED IMAM RABBANI; KSHAMA DEVI; SALMA KHANAM (International Journal of Pharma and Bio Sciences, 2010)
The anti-mutagenic activity of a PPAR-γ ligand pioglitazone (PIO-1 and 10 mg/kg, p.o daily for 4 weeks) was evaluated against the nicotinamide (NA-230 mg/kg, ip) and streptozotocin (STZ-65 mg/kg, ip) induced nuclear damage in diabetic Wistar rats. The NA-STZ diabetes significantly (P<0.001) increased the frequency of bone marrow micronuclei in erythrocytes and reduced the P/N ratio (polychromatic: normochromatic erythrocytes ratio) besides diminishing the serum antioxidant enzymes level. PIO at 10 mg/kg reduced (P<0.001) the incidences of micronuclei in erythrocytes as well increased (P<0.05) the P/N ratio in diabetic rats. The antioxidant study indicated that the higher dose of PIO (10 mg/kg) significantly (P<0.01) increased the SOD and catalase level, while the lower dose (1 mg/kg) enhanced (P<0.05) only the catalase level compared to the diabetic group. The results suggest that the inhibitory effect of PIO against the NA-STZ induced DNA damage could be due to its ability to enhance the antioxidant defense.